Evaluation of lamina cribrosa curvature index in different types of glaucoma - Canleblebici, Mehmet; Celiker, Ulku; Yildirim, Hakan; Balbaba, Mehmet (Springer, 2024)
ObjectiveThe aim of this study was to evaluate the lamina cribrosa curvature index in different types of glaucoma in comparison with clinical findings and conventional measurement methods.Material and methodPatients older than 18 years who were followed up in Glaucoma Unit of Department of Ophthalmology at F & imath;rat University Faculty of Medicine, whose disease had been under control at least for 1 year, who had at least three reliable visual fields, whose refractive error was between - 6 and + 5 diopter and who did not have any disease other than glaucoma that would affect the visual field, were included in the study. Clinical and demographic characteristics, visual field, optical coherence tomography and lamina cribrosa curvature index (LCCI) results were evaluated. The study patients were divided into six groups: early-stage primary open-angle glaucoma (POAG) as group 1 and intermediate-advanced stage POAG as group 2, pseudo-exfoliation glaucoma (PEXG) as group 3, normal tension glaucoma (NTG) as group 4, ocular hypertension patients whom subsequently developed POAG as group 5 and healthy control as group 6.ResultsA total of 189 eyes of 101 patients were included in our study. Forty-seven patients were male (46.5%) and 54 were female (53.5%). The mean age was 62.43 +/- 1.49 years. LCCI, mean deviation (MD), visual field index (VFI), pattern standard deviation (PSD) and retinal nerve fiber layer thickness (RNFL) values were analyzed in all groups and Pearson correlation analysis showed statistically significant correlation between PSD and RNFL measurements with LCCI values in all groups. MD value was correlated with LCCI in groups 2, 3 and 4, while VFI value was correlated with LCCI in all groups except group 5. When the groups were compared with each other according to the Post-Hoc Tamhane test, LCCI measurement showed statistically significant results in accordance with MD, VFI, PSD and RNFL values.ConclusionThe LCCI assessment is mostly consistent with conventional tests. In this study, in which different types of glaucoma and healthy subjects were examined simultaneously, LCCI shows promise as a detailed and reliable assessment method.
Keywords: Glaucoma; Lamina cribrosa curvature index; Open angle glaucoma; Normal tension glaucoma; Pseudo-exfoliative glaucoma